Agricultural Investment for Development Analyzer tool designed to help governments and donors prioritize agricultural investments in the Middle East and North Africa - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The investment datasets were finalized for Egypt, Jordan, Tunisia and Yemen. The development of the online tools was completed for Egypt, Tunisia and Yemen, with Jordan to follow in 2021. Trainings have started with partners and several publications are available. Official launches are taking place in 2021.